2019
DOI: 10.18280/ijht.370420
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Biomass Pellet Combustion Process

Abstract: According to computational fluid dynamics, heat transfer theory, and chemical reaction kinetics theory, the models of single-pellet biomass combustion were established, flow, heat transfer and mass transfer of single-particle biomass fuel during combustion were analog calculated, and they showed about 2 min, a 2 cm biomass pellet fuel completely burnt out , the highest temperature is 1280 k, the release of gases such as H2O, CO2 and CO. The bed combustion model of biomass chain furnace was built based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It can be observed that from 16 to 32 min the burn rate is in the range between 20 and 22.5 g/min. In this period, the maximum amount of volatiles is removed from the biomass pellets . After 32 min, there is a decrease in the burn rate steadily up to the end of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that from 16 to 32 min the burn rate is in the range between 20 and 22.5 g/min. In this period, the maximum amount of volatiles is removed from the biomass pellets . After 32 min, there is a decrease in the burn rate steadily up to the end of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In this period, the maximum amount of volatiles is removed from the biomass pellets. 35 After 32 min, there is a decrease in the burn rate steadily up to the end of the experiment. As we can see, the burn rate profile is different for the three WBT experiments.…”
Section: Thermal Performance Analysis Of Model Ementioning
confidence: 99%
“…It can also be processed into renewable tableware [189], not necessarily as a fuel or energy source. Even if biomass is used as an energy source, it does not necessarily have to be made into liquid fuels, but can also be used in other forms of energy such as direct combustion [190], hydrogen production, or gas. Therefore, if liquid fuel preparation is to guarantee its stable feedstock supply, it needs to have higher financial benefits, which might be significantly affected by the market.…”
Section: Feedstock Supplymentioning
confidence: 99%
“…A flow, heat transfer, and mass transfer mathematical model was used to investigate the burning characteristics of a biomass pellet. 19 A pellet of 20 mm diameter burned completely in 2 min, and a maximum temperature of 1280 K was found. In conditions like those of practical industrial combustors, an experimental investigation was conducted to examine the ignition characteristics of solid biomass particles of various shapes and sizes.…”
Section: Introductionmentioning
confidence: 98%
“…The remaining char ignited and burned as a result of the volatiles being released and burning into spherical envelope flames. A flow, heat transfer, and mass transfer mathematical model was used to investigate the burning characteristics of a biomass pellet . A pellet of 20 mm diameter burned completely in 2 min, and a maximum temperature of 1280 K was found.…”
Section: Introductionmentioning
confidence: 99%